Peran Kompetensi Individu terhadap Kinerja Karyawan pada PT Berkah Industri Mesin Angkat (BIMA) Surabaya - Fitria Agustina; Mochammad Isa Anshori (JURNAL RISET MANAJEMEN (JURMA), 2024)
Competence has a very important role, because competence generally concerns the expertise of an employee where this expertise can support the success and performance level of employees, besides that the level of employee performance can affect the level of performance of a company as well. This research uses the literature review study method by looking for sources from articles, books and other research. This research focuses on the competencies possessed by employees of PT Berkah Industri Mesin Angkat (BIMA) in Surabaya, that individual competence is very important as a support for the success of a company.